Risk of drug-induced angioedema: a pharmacovigilance study of FDA adverse event reporting system database - Fan, Maoxia; Niu, Kaibin; Wu, Xiaoqi; Shi, Hongshuo (Frontiers in Pharmacology, 2024)
The purpose of this study is to explore and analyze the FDA Adverse Event Reporting System (FAERS) database to identify drug adverse reaction signals associated with angioedema. The findings aim to provide valuable insights for clinical drug safety considerations. Methods: The Open Vigil 2.1 data platform was utilized to collect adverse event reports related to angioedema from the first quarter of 2004 to the fourth quarter of 2023. The reporting odds ratio (ROR) and proportional reporting ratio (PRR) were employed as disproportionality measures to detect adverse reaction signals of drugs associated with angioedema. Results: A total of 38,921 reports were retrieved, with the majority being reported by healthcare professionals. The analysis included predominantly adult patients (≥18 years of age), with slightly higher representation of females compared to males. Among the top 30 drugs associated with the occurrence of angioedema, 24 drugs showed positive signals in the risk analysis.Based on the individual drug ROR (95% CI) as a measure of risk signal strength, the top 5 drugs are as follows: lisinopril [ROR (95% CI): 46.43 (42.59-50.62)], enalapril [ROR (95% CI): 43.51 (39.88-47.46)], perindopril [ROR (95% CI): 31.17 (27.5-35.32)], alteplase [ROR (95% CI): 29.3 (26.95-31.85)], ramipril [ROR (95% CI): 20.93 (19.66-22.28)]. After categorizing the drugs, the strongest positive signal was observed in the antithrombotic agents [ROR (95% CI): 22.53 (21.16-23.99)], following that, cardiovascular drugs [ROR (95% CI): 9.17 (8.87-9.48)], antibiotics [ROR (95% CI): 6.42 (5.91-6.96)], immunosuppressors [ROR (95% CI): 5.95 (5.55-6.39)], anti-inflammatory analgesics [ROR (95% CI): 4.65 (4.45-4.86)], antiallergic drugs [ROR (95% CI): 4.47 (3.99-5)], antiasthmatics [ROR (95% CI): 2.49 (2.14-2.89)], blood sugar control drugs [ROR (95% CI): 1.65 (1.38-1.97)], and digestive system drugs [ROR (95% CI): 1.59 (1.45-1.74)] exhibited progressively decreasing ROR values. Conclusion: Many medications are associated with a high risk of angioedema. These medications play a crucial and potentially preventable role in controlling the occurrence of angioedema. It is essential to consider the risk level of drug-induced angioedema in clinical practice to optimize medication therapy.